Human pancreatic cancer fusion 2 (HPC2) 1‐B3: A novel monoclonal antibody to screen for pancreatic ductal dysplasia. Issue 1 (18th July 2012) - Morgan, Terry K.; Hardiman, Karin; Corless, Christopher L.; White, Sandra L.; Bonnah, Robert; Van de Vrugt, Henry; Sheppard, Brett C.; Grompe, Markus; Cosar, Ediz F.; Streeter, Philip R.
Abstract BACKGROUND. Pancreatic ductal adenocarcinoma is rarely detected early enough for patients to be cured. The objective of the authors was to develop a monoclonal antibody to distinguish adenocarcinoma and precancerous intraductal papillary mucinous neoplasia (IPMN) from benign epithelium. METHODS. Mice were immunized with human pancreatic adenocarcinoma cells and monoclonal antibodies were screened against a panel of archived pancreatic tissue sections, including pancreatitis (23 cases), grade 1 IPMN (16 cases), grade 2 IPMN (9 cases), grade 3 IPMN (13 cases), and various grades of adenocarcinoma (17 cases). One monoclonal antibody, human pancreatic cancer fusion 2 (HPC2) 1‐B3, which specifically immunostained adenocarcinoma and all grades of IPMN, was isolated. Subsequently, HPC2 1‐B3 was evaluated in a retrospective series of 31 fine‐needle aspiration (FNA) biopsies from clinically suspicious pancreatic lesions that had long‐term clinical follow‐up. RESULTS. HPC2 1‐B3 was negative in all 31 cases of chronic pancreatitis that were tested. In contrast, HPC2 1‐B3 immunostained the cytoplasm and luminal surface of all 16 well‐ to moderately differentiated pancreatic ductal adenocarcinomas. It demonstrated only weak focal staining of poorly differentiated carcinomas. All high‐grade IPMNs were found to be positive for HPC2 1‐B3. The majority of low‐grade to intermediate‐grade IPMNs were positive (66% of cases). Immunostaining a separate series of pancreatic FNA cell blocks for HPC2 1‐B3 demonstrated that the relative risk for detecting at least low‐grade dysplasia (2.0 [95% confidence interval, 1.23‐3.26]) was statistically significant (P = .002 by the Fisher exact test). CONCLUSIONS. To reduce the mortality of pancreatic cancer, more effective early screening methods are necessary. The data from the current study indicate that a novel monoclonal antibody, HPC2 1‐B3, may facilitate the diagnosis of early pancreatic dysplasia. Cancer (Cancer Cytopathol) 2013;121:37–46 © 2012 American Cancer Society.